2014
DOI: 10.1016/j.foodchem.2014.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Lactobacillus rhamnosus GG in prebiotic edible films

Abstract: HighlightsThe concept of prebiotic gelatine based edible films containing probiotics is presented.Prebiotic edible films effectively protected L. rhamnosus GG.Inulin and wheat fibre improved the storage stability of L. rhamnosus GG.Glucose-oligosaccharides and polydextrose reduced lethality during air drying.Prebiotics resulted in a more compact, less porous and reticular film structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
89
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 35 publications
15
89
1
8
Order By: Relevance
“…3). Corroborating our previous findings (Soukoulis et al., 2014b), FIB-SEM allowed the successful visualisation of the cells of L. rhamnosus GG embedded in the biopolymer matrices (see Fig. 3).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…3). Corroborating our previous findings (Soukoulis et al., 2014b), FIB-SEM allowed the successful visualisation of the cells of L. rhamnosus GG embedded in the biopolymer matrices (see Fig. 3).…”
Section: Resultssupporting
confidence: 92%
“…Film opacity was not significantly (p > 0.05, data not shown) affected by the presence of probiotic cells in line with our previous findings (Soukoulis et al., 2014b), furthermore κ-CAR/LBG and HSA based films exhibited the highest opacity which is presumably due to the lower solids contents of the κ-CAR/LBG and HSA based forming solutions. Film opacity significantly (p < 0.05) increased in the presence of WPC.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Several authors have reported that prebiotics can be used as a functional ingredient in edible films employing different polymeric matrices, such as starch (Tang et al, 2015), methylcellulose (Romano, Tavera-Quiroz, Bertola, Mobili, Pinotti & Gómez-Zavaglia, 2014;Tavera-Quiroz, Romano, Mobili, Pinotti, Gómez-Zavaglia & Bertola, 2015) or gelatin (Soukoulis, Behboudi-Jobbehdar, Yonekura, Parmenter & Fisk, 2014); however, in all published works, prebiotics have been obtained from commercial sources (extracted from plants), and in this work bacterial FOSs were employed to produce edible films.…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulation in alginate matrix was shown to enhance survival of several probiotic strains upon exposure to acidic conditions and mild heat treatment (Ding and Shah, 2007). Addition of prebiotic oligosaccharides to edible films was found to further enhance the survival of beneficial microbes during dehydration and storage (Soukoulis et al, 2014).…”
Section: Encapsulationmentioning
confidence: 99%